Peran Komunikasi dalam Proses Pengambilan Keputusan Bermigrasi - Lusia Handayani; Sarwititi Sarwoprasodjo; Krishnarini Matindas (Institut Pertanian Bogor, 2017)
This case study aimed to analyze the role of communication in migration decision making process, how did information seeking and meaning construction of fantasy themes encourage migration decision making. The subject of this research was the migrant youth group of Rejosari Village, Yogyakarta. The research was qualitative method using fantasy theme analysis. Fantasy theme is derived from Symbolic Convergence Theory that sees how narration can construct fantasy themes in migrating behavior. This research found that the fantasy themes emerged from the narration constructed a new meaning that is decision making. The group is considered as a credible source of information about migration rather than their families. Although they do not exclude the role of the family on migration decisions. The group has an important role in supporting and sustaining individual decision-making.